Disc battery in the pediatric oesophagus - Mubjal, Manish; Tuli, Nitika; Rishi, Porshia; Singh, Harjinder; Munjal, Shubham (International Journal of Contemporary Pediatrics, 2020)
The wide usage of disc batteries in toys, in the late seventies presented a new problem. In the form of accidental lodgements in the pediatric aerodigestive tract. The physico-chemical nature of the disc battery necessitates an early removal, so as to avoid a fatal outcome if missed and retained for a long duration. Management of one such case is reported with radiographic documentation.